1997
DOI: 10.1210/endo.138.3.4983
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Specific Alterations in the Expression of the Insulin-Like Growth Factor System during Early Placental Development in the Ewe1

Abstract: The placenta is recognized as an important determinant of fetal growth rate, yet the factors regulating its proliferation remain poorly understood. Components of the insulin-like growth factor (IGF) system were localized in the ovine uterus using in situ hybridization between days 13-55 of gestation, the period of implantation and placentome formation. IGF-II messenger RNA (mRNA) expression was intense in the fetal mesoderm, particularly at the tips of the invading placentome villi. Moderate levels of IGF-II m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Reductions in IGF1 concentrations are associated with glucose insufficiency in ewes, which results in a shift in nutrient partitioning (Tygesen et al, 2008). Although intact IGF1 does not cross the placenta, increases in IGF1 concentrations may stimulate placental growth through IGF1 receptors (Browne and Thorburn, 1989;Reynolds et al, 1997). Such a compensatory response in IGF1 levels after switching from E+ to E− treatment may be an attempt to stimulate placental development and rescue fetal growth.…”
Section: Serum Hormone Concentrationsmentioning
confidence: 99%
“…Reductions in IGF1 concentrations are associated with glucose insufficiency in ewes, which results in a shift in nutrient partitioning (Tygesen et al, 2008). Although intact IGF1 does not cross the placenta, increases in IGF1 concentrations may stimulate placental growth through IGF1 receptors (Browne and Thorburn, 1989;Reynolds et al, 1997). Such a compensatory response in IGF1 levels after switching from E+ to E− treatment may be an attempt to stimulate placental development and rescue fetal growth.…”
Section: Serum Hormone Concentrationsmentioning
confidence: 99%
“…IGF-II is a polypeptide mitogen related to insulin that is believed to be particularly important during placental and embryonic development (3)(4)(5)(6). The binding sites for IGF-II and mannose 6-phosphate-bearing ligands have been shown to be distinct (7)(8)(9).…”
mentioning
confidence: 99%
“…Terefore, examining the post-natal development and adult productivity of lambs obtained from ewes mating in different seasons can be an essential contributor to revealing the efects of seasonal diferences in placental characteristics on the productivity of animals in the adult period. Previous studies have reported that IGFs are expressed and secreted by the sheep uterus and placenta [48,49]. IGF-I and IGF-II mRNAs were detected in sheep embryos throughout pre-implantation development from the singlecell stage to the blastocyst stage [50].…”
Section: Discussionmentioning
confidence: 90%
“…IGF-I and IGF-II mRNAs were detected in sheep embryos throughout pre-implantation development from the singlecell stage to the blastocyst stage [50]. Following implantation, maternal uterine IGF-I mRNA expression was low, making it unlikely that locally expressed and produced IGF-I is essential for placental development [49]. In contrast, expression of IGF-II mRNA in the placentome capsule and endometrial stroma continued throughout the frst half of pregnancy, and IGF-II mRNA expression increased in foetal mesodermal tissues from days 14 to 35 and remained elevated until birth [51].…”
Section: Discussionmentioning
confidence: 99%